2004
DOI: 10.1128/mcb.24.6.2526-2535.2004
|View full text |Cite
|
Sign up to set email alerts
|

Np95 Is a Histone-Binding Protein Endowed with Ubiquitin Ligase Activity

Abstract: Np95 is an important determinant in cell cycle progression. Its expression is tightly regulated and becomes detectable shortly before the entry of cells into S phase. Accordingly, Np95 is absolutely required for the G 1 /S transition. Its continued expression throughout the S/G 2 /M phases further suggests additional roles. Indeed, Np95 has been implicated in DNA damage response. Here, we show that Np95 is tightly bound to chromatin in vivo and that it binds to histones in vivo and in vitro. The binding to his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
177
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(182 citation statements)
references
References 59 publications
(81 reference statements)
5
177
0
Order By: Relevance
“…In addition to regulating the transcription of TOP2A (28) and RB1 (23), UHRF1 has been shown to possess E3 ubiquitin ligase activity targeting histone H3 (29) and itself (24), yet the functional relevance of monoubiquitinization of these targets is unknown. Loss of UHRF1 function abrogates S phase entry, and its overexpression shortens the cell cycle (22)(23)(24)46), in agreement with our finding that uhrf1 is up-regulated during regeneration in parallel with ccna2 and is required for hepatocyte proliferation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to regulating the transcription of TOP2A (28) and RB1 (23), UHRF1 has been shown to possess E3 ubiquitin ligase activity targeting histone H3 (29) and itself (24), yet the functional relevance of monoubiquitinization of these targets is unknown. Loss of UHRF1 function abrogates S phase entry, and its overexpression shortens the cell cycle (22)(23)(24)46), in agreement with our finding that uhrf1 is up-regulated during regeneration in parallel with ccna2 and is required for hepatocyte proliferation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In this point of view, accumulating evidences have shown that UHRF1 acts as a multi-modular protein involved in the maintenance of the chromatin status and its propagation during cell division. Indeed, UHRF1 binds to methylated DNA and recruits DNA methyltransferase 1 (DNMT1) and histone deacetylase 1 (HDAC1) through the SRA (SET and RING finger Associated) domain [13,[16][17][18][19]. These protein-protein interactions precede S phase entry and could be required for cell cycle progression [10,20].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, ICBP90 contains an ubiquitinlike domain (NIRF_N), a SRA (set and ring-associated domain, also known as G9a or YDG domain) and two zinc finger domains, a plant homeo domain (PHD) and a really interesting new gene (RING) domain, both of which are hallmarks of E3 ligases (Ingham et al, 2004;Ohta and Fukuda, 2004). The RING finger of ICBP90 exhibits E3 ligase activity (Jenkins et al, 2005) as does that of the mouse ICBP90 orthologue, Np95 (Citterio et al, 2004).…”
Section: Ink4amentioning
confidence: 99%